B cells producing type i IFN modulate macrophage polarization in tuberculosis - Bénard, Alan (2018)
In addition to their well-known function as antibody-producing cells, B lymphocytes can markedly influence the course of infectious or noninfectious diseases via antibody-independent mechanisms. In tuberculosis (TB), B cells accumulate in lungs, yet their functional contribution to the host response remains poorly understoo